Short-Term and Long-Term Effectiveness of Intensive Interdisciplinary Pain Treatment for Children and Adolescents with Chronic Headache: A Longitudinal Observation Study - Meltem Dogan; Boris Zernikow; Julia Wager (MDPI AG, 2021)
Pediatric chronic headache causes significant impairment to those affected and bears the risk of aggravation into adulthood. Intensive interdisciplinary pain treatment (IIPT) was found to positively affect pain-related and emotional outcomes in pediatric patients with chronic pain up to 4 years after treatment. This study was aimed at investigating the effect of IIPT on solely pediatric chronic headache patients. As part of a longitudinal observation study, n = 70 children and adolescents with chronic headache receiving IIPT were included, of which n = 47 completed the assessment at four assessment time points: before treatment (PRE) and at three follow-ups (6-MONTH FOLLOW-UP, 1-YEAR FOLLOW-UP, and 4-YEAR FOLLOW-UP). Pain-related (pain intensity, pain-related disability, school absence), as well as psychological outcome domains (anxiety, depression), were investigated. The results support the short-term and long-term efficacy of IIPT for pediatric chronic headache patients regarding the pain-related outcome measures by significant reductions from PRE to all follow-up measure points. For anxiety and depression, only short-term improvements were found. Future studies should specifically focus on the identification of methods to consolidate the beneficial short-term effects of IIPT on psychological outcome domains in the long term.